Enterprise risk management in today's world : enterprise-wide risk management and strategy - Louisot, Jean-Paul (Emerald Publishing Limited, 2024)
In recent years events such as a global pandemic, huge technological changes, and war in Europe have demonstrated how organizations manage risk is more important than ever. Plans, models and ideas to mitigate disruptive situations are needed to ensure future success. Enterprise Risk Management in Today's World examines enterprise risk management in its past, present and future, exploring the role that directors and leaders in organizations have in devising risk management strategies, analysing values such as trust, resilience, CSR and governance within organizations. Benefiting students, researchers and high-level decision makers, this volume fills a gap in the existing literature of the interaction between business and society in the field of enterprise risk management. Emerald Studies in Finance, Insurance, and Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.
Keywords: Business enterprises -- Risk management.; Risk management.; Strategic planning.; Business & Economics -- Finance -- Financial Risk Management.; Small businesses and self-employment.; Finance and the finance industry.; Risk assessment.; elektronické knihy; electronic books